ZTA ceramic substrate and preparation method and application thereof
Through microwave-assisted reaction and grinding process optimization, ZTA ceramic substrates with high thermal conductivity and good mechanical properties were prepared, which solves the problems of low thermal conductivity and complex process of traditional materials, meets the needs of high heat dissipation applications and reduces costs.
Patent Information
- Application Number
- CN202411759361.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
While improving toughness and bending strength, traditional ZTA ceramic materials have low thermal conductivity, which is difficult to meet the needs of high heat dissipation applications, and the preparation process is complex and costly.
The ZTA powder is prepared by microwave-assisted reaction, and the average particle size and distribution of the powder are regulated through the grinding process, and the casting and sintering process are optimized to improve the uniformity and toughness of the material while reducing process costs.
It achieves the balance of high thermal conductivity and good mechanical properties of ZTA ceramic substrates, meets the needs of high heat dissipation applications such as high-power electronic modules and semiconductor packaging, and simplifies the process flow and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of advanced ceramic materials, and in particular to a ZTA ceramic substrate and a preparation method and application thereof. Background Art
[0002] With the miniaturization, high power density and high heat dissipation requirements of modern electronic devices, substrate materials need to have excellent mechanical properties, thermal conductivity and electrical insulation. Traditional alumina ceramics are widely used in electronic substrates due to their low cost, high mechanical strength and strong chemical stability, but their insufficient toughness and easy cracking limit their use in some high-reliability products.
[0003] In order to solve the brittleness problem of alumina ceramics, researchers have developed zirconia-toughened alumina (ZTA) composites, which achieve toughening effects by introducing zirconia particles into the alumina matrix. The phase change toughening mechanism of zirconia can absorb energy under stress and improve the fracture toughness of the material. With the development of nanotechnology, the performance of ZTA composites has been further improved, especially in terms of uniformity of particle distribution and optimization of sintering process. At present, ZTA composites have been widely used in aerospace, military electronics and high-power power modules, and have gradually become one of the preferred materials for electronic device packaging.
[0004] The traditional method directly mixes zirconium oxide particles into alumina ceramics to form ZTA composite materials, and uses the stress-induced phase change effect of zirconium oxide to improve the toughness and flexural strength of alumina ceramics. However, the traditional method still has some limitations: 1) Limited toughening effect: zirconium oxide particles are unevenly distributed in the matrix and are prone to agglomeration, which limits the fracture toughness of the material, especially in the stress concentration area, the material may still break; 2) Thermal conductivity and mechanical properties cannot be achieved at the same time: When improving the toughness of ceramics, the thermal conductivity is usually degraded. Although the mechanical properties of ZTA ceramics are improved compared to alumina, its thermal conductivity is low. In high temperature environments, its thermal conductivity is not enough to meet the needs of high heat dissipation applications, such as high-power electronic modules and semiconductor packaging; 3) The sintering process is complicated and costly: The preparation process of ZTA materials is complicated. During the sintering process, the thermal expansion coefficients of different materials vary greatly, which easily leads to sintering defects, increasing the difficulty of process control and production costs, while reducing the stability and reliability of the material. Summary of the invention
[0005] Based on this, the main purpose of this application is to provide a method for preparing a ZTA ceramic substrate. The method has a simple process, can ensure the reliability of the material and reduce the process cost, and can prepare a ZTA ceramic substrate with good thermal conductivity and mechanical properties to meet the use requirements of high-heat dissipation applications such as high-power electronic modules and semiconductor packaging.
[0006] In a first aspect of the present application, a method for preparing a ZTA ceramic substrate is provided, comprising the following steps:
[0007] Dispersing zirconium salt and aluminum salt in water to prepare a dispersion; adding a surfactant to the dispersion and mixing to prepare a precursor solution;
[0008] subjecting the precursor solution to a microwave-assisted reaction to prepare a reaction solution;
[0009] Separating the reaction liquid into solid and liquid, taking the solid product and calcining and crushing it to prepare the first powder;
[0010] Mixing the first powder with aluminum oxide to prepare a second powder;
[0011] adding a dispersing medium to the second powder and grinding to prepare a third powder;
[0012] Dispersing the third powder, the binder, the plasticizer and the additive in water to prepare a slurry;
[0013] The slurry is tape-casted, dried, and sintered to prepare the ZTA ceramic substrate.
[0014] In some embodiments, the zirconium salt includes at least one of zirconium oxychloride, zirconium oxysulfate, zirconium nitrate, zirconium acetate, zirconium sulfate, and zirconium chloride;
[0015] and / or the aluminum salt comprises at least one of ammonium aluminum sulfate, aluminum nitrate and aluminum chloride;
[0016] And / or the surfactant includes at least one of polyvinyl pyrrolidone, polyacrylic acid, polyacrylate, polyethylene glycol and polyvinyl alcohol.
[0017] In some embodiments, the mass ratio of the zirconium salt to the aluminum salt is 80:20-95:5; the added amount of the surfactant is 2-5wt% of the dispersion; and the solid dosage of the dispersion is 10-40wt%.
[0018] In some embodiments, in the second powder, the amount of zirconium oxide is 6-12wt%;
[0019] And / or the mass ratio of the second powder to the dispersion medium is 1:0.15-1:0.5.
[0020] In some embodiments, the dispersion medium includes water, a first dispersant, and a defoaming agent;
[0021] Optionally, in the dispersion medium, in terms of mass percentage, the amount of water is 75-90%, the amount of the first dispersant is 5-20%, and the amount of the defoaming agent is 3-10%.
[0022] In some embodiments, the binder includes at least one of polyvinyl alcohol, styrene-acrylic latex, and acrylic latex;
[0023] And / or the plasticizer includes C3-C 10 Polyols;
[0024] And / or the auxiliary agent includes at least one of a second dispersant, a water retaining agent and a thickener.
[0025] In some embodiments, in the slurry, based on the mass percentage of the slurry as 100%, the amount of the third powder is 40-50%, the amount of the binder is 15-25%, the amount of the plasticizer is 0.5-4%, the amount of the auxiliary agent is 2-10%, and the amount of water is the balance.
[0026] In some embodiments, the average particle size of the first powder is 3-15 μm;
[0027] And / or the specific surface area of the third powder is 6-10m² / g, and the average particle size of the third powder is 0.1-0.5µm.
[0028] In some embodiments, the conditions of the microwave-assisted reaction include: microwave frequency 2-3 GHz, microwave power 800-1200 W, reaction temperature 120-180° C. and reaction time 20-60 min.
[0029] In some embodiments, the calcination conditions include: a calcination temperature of 1000-1400° C. and a calcination time of 2-6 hours.
[0030] In some embodiments, the grinding comprises ball milling and / or sand milling.
[0031] In some embodiments, the sintering conditions include: a sintering temperature of 1400-1700° C. and a sintering time of 1-3 hours.
[0032] In some embodiments, the sintering step further includes a polishing step; optionally, the roughness of the ZTA ceramic substrate is ≤0.1 μm.
[0033] The second aspect of the present application provides a ZTA ceramic substrate prepared by the aforementioned preparation method.
[0034] The third aspect of the present application provides the application of the aforementioned ZTA ceramic substrate in high-power electronic modules and semiconductor packaging.
[0035] The beneficial effects of this application are:
[0036] 1. The present application provides a method for preparing a ZTA ceramic substrate. The method has a simple process, can ensure the reliability of the material and reduce the process cost, and can prepare a ZTA ceramic substrate with good thermal conductivity and mechanical properties, which meets the use requirements of high-heat dissipation applications such as high-power electronic modules and semiconductor packaging.
[0037] 2. Microwave-assisted reaction is used to prepare ZTA powder, which improves reaction efficiency and powder uniformity and avoids agglomeration; the average particle size of the powder is finely controlled through the grinding process to ensure the uniformity and adaptability of the powder; the particle distribution and grain growth control are optimized during the casting and sintering process, effectively inhibiting grain growth and further toughening the material. Combining the above factors, the mechanical properties such as toughness of the material are improved, and the material is given excellent thermal conductivity. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with specific embodiments. Preferred embodiments of the present application are provided hereinafter. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0040] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0041] In this article, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the quantity of the indicated technical features.
[0042] In the description herein, "at least one" means more than one, including one or more than two, for example, one, two, three, etc., unless otherwise clearly defined.
[0043] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0044] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 500-600rpm means that the units of the left endpoint "500" and the right endpoint "600" are both rpm (revolutions per minute).
[0045] The temperature parameters herein, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows for temperature fluctuations within the precision range of instrument control.
[0046] One aspect of the present application, the first aspect of the present application, provides a method for preparing a ZTA ceramic substrate, comprising the following steps:
[0047] Dispersing zirconium salt and aluminum salt in water to prepare a dispersion; adding a surfactant to the dispersion and mixing to prepare a precursor solution;
[0048] subjecting the precursor solution to a microwave-assisted reaction to prepare a reaction solution;
[0049] Separating the reaction liquid into solid and liquid, taking the solid product and calcining and crushing it to prepare the first powder;
[0050] Mixing the first powder with aluminum oxide to prepare a second powder;
[0051] adding a dispersing medium to the second powder and grinding to prepare a third powder;
[0052] Dispersing the third powder, the binder, the plasticizer and the additive in water to prepare a slurry;
[0053] The slurry is tape-casted, dried, and sintered to prepare the ZTA ceramic substrate.
[0054] The present application provides a method for preparing a ZTA ceramic substrate. The method has a simple process, can ensure the reliability of the material and reduce the process cost, and can prepare a ZTA ceramic substrate with good thermal conductivity and mechanical properties, which meets the use requirements of high-heat dissipation applications such as high-power electronic modules and semiconductor packaging.
[0055] Specifically, microwave-assisted reaction is used to prepare ZTA powder, which improves reaction efficiency and powder uniformity and avoids agglomeration; the average particle size of the powder is finely controlled through the grinding process to ensure the uniformity and adaptability of the powder; the particle distribution and grain growth control are optimized during the casting and sintering process, effectively inhibiting grain growth and further toughening the material. The above factors are combined to improve the mechanical properties of the material, such as toughness, and give the material excellent thermal conductivity.
[0056] In some embodiments, the zirconium salt includes at least one of zirconium oxychloride, zirconium oxysulfate, zirconium nitrate, zirconium acetate, zirconium sulfate, and zirconium chloride;
[0057] and / or the aluminum salt comprises at least one of ammonium aluminum sulfate, aluminum nitrate and aluminum chloride;
[0058] And / or the surfactant includes at least one of polyvinyl pyrrolidone, polyacrylic acid, polyacrylate, polyethylene glycol and polyvinyl alcohol.
[0059] It is understandable that the zirconium salt and the aluminum salt can be hydrates of the corresponding salts, and the specific types of the zirconium salt and the aluminum salt are not particularly limited. Among them, zirconium oxychloride and aluminum nitrate are inexpensive and are more preferred from an economic point of view. The zirconium salt, the aluminum salt and the surfactant can be used alone or in combination. The surfactant is used to improve the uniformity and particle dispersibility of the precursor solution, and there is no special requirement for the specific type.
[0060] It is understandable that when the precursor solutions are mixed, they can be heated and stirred, for example, stirred at 50-70° C. until the solution is completely clarified, to ensure that the precursor solution is uniform and provide an ideal chemical basis for subsequent microwave treatment.
[0061] In some embodiments, the mass ratio of the zirconium salt to the aluminum salt is 80:20-95:5; the amount of the surfactant added is 2-5wt% of the dispersion; and the solid content of the dispersion is 10-40wt%. Specifically, the molar ratio of the zirconium salt to the aluminum salt can be 80:20, 81:19, 82:18, 83:17, 84:16, 85:15, 86:14, 87:13, 88:12, 89:11, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, etc.; the amount of the surfactant added can be 2wt%, 3wt%, 4wt%, 5wt%, etc. of the dispersion; and the solid content of the dispersion can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc.
[0062] In some embodiments, the amount of zirconium oxide in the second powder is 6-12wt%, specifically 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, etc.
[0063] In some embodiments, the mass ratio of the second powder to the dispersion medium is 1:0.15-1:0.5, specifically 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, etc.
[0064] In some embodiments, the dispersion medium includes water, a first dispersant, and a defoaming agent;
[0065] Optionally, in the dispersion medium, in terms of mass percentage, the amount of water is 75-90%, the amount of the first dispersant is 5-20%, and the amount of the defoaming agent is 3-10%.
[0066] In some embodiments, the binder includes at least one of polyvinyl alcohol, styrene-acrylic latex, and acrylic latex;
[0067] In some embodiments, the plasticizer comprises C3-C 10 Polyol; specifically, the C3-C 10 The polyol may include glycerol, propylene glycol, ethylene glycol, 1,1,1-trimethylolpropane, etc. Preferably, the C3-C 10 The polyol is glycerol.
[0068] And / or the auxiliary agent includes at least one of a second dispersant, a water retaining agent and a thickener.
[0069] It is understandable that there is no special requirement for the types of the first dispersant, the second dispersant, the defoamer, the water retainer and the thickener, as long as the corresponding effects can be achieved. Preferably, the first dispersant and the second dispersant each independently include at least one of a sulfonate dispersant, a polycarboxylic acid dispersant and an acrylic resin dispersant; the defoamer includes at least one of an organosilicon defoamer, a polyether defoamer, a fatty acid defoamer and a polyacrylic acid defoamer; the water retainer includes at least one of a polyacrylamide water retainer, a starch grafted water retainer, a cellulose water retainer and cyclohexanone, such as hydroxypropyl methylcellulose and / or cyclohexanone; the thickener includes a cellulose thickener, such as sodium carboxymethyl cellulose.
[0070] In some embodiments, in the slurry, based on the mass percentage of the slurry as 100%, the amount of the third powder is 40-50%, the amount of the binder is 15-25%, the amount of the plasticizer is 0.5-4%, the amount of the auxiliary agent is 2-10%, and the amount of water is the balance.
[0071] In some embodiments, the average particle size of the first powder is 3-15 μm;
[0072] And / or the specific surface area of the third powder is 6-10m² / g, and the average particle size of the third powder is 0.1-0.5µm.
[0073] It can be understood that microwave treatment helps to improve reaction efficiency, avoid particle agglomeration, and improve the purity and uniformity of powders. There are no special requirements for microwave treatment conditions. In some embodiments, the conditions of the microwave-assisted reaction include: microwave frequency 2-3 GHz, microwave power 800-1200 W, reaction temperature 120-180 ° C and reaction time 20-60 min; specifically, the microwave frequency can be 2 GHz, 2.1 GHz, 2.2 GHz, 2.3 GHz, 2.4 GHz, 2.5 GHz, 2.6 GHz, 2.7 GHz, 2.8 GHz, 2.9 GHz, 3.0 GHz, the microwave power can be 800 W, 850 W, 900 W, 950 W, 1000 W, 1050 W, 1100 W, 1150 W, 1200 W, etc., the reaction temperature can be 120 ° C, 130 ° C, 140 ° C, 150 ° C, 160 ° C, 170 ° C, 180 ° C, etc., and the reaction time can be 20 min, 30 min, 40 min, 50 min, 60 min, etc.
[0074] By calcining, organic matter and crystal water in the solid product can be removed to improve the purity. The calcination conditions are not particularly limited. In some embodiments, the calcination conditions include: a calcination temperature of 1000-1400°C, a calcination time of 2-6h, specifically, the calcination temperature can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, etc.; the calcination time can be 2h, 2.5h, 3h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.
[0075] Grinding can finely control the average particle size of the powder, ensure the uniformity of the average particle size of the powder, and improve the adaptability of the subsequent casting process. The grinding method is not particularly limited. In some embodiments, the grinding includes ball milling and / or sand milling. It is understandable that one-stage grinding or two-stage grinding can be used. The two-stage grinding can firstly break up large particles by ball milling, and then further refine the average particle size by sand milling.
[0076] It is understandable that the viscosity of the slurry can be adjusted according to actual needs. Preferably, the viscosity of the slurry is 1000-3000 cP, and more preferably, 1500-2000 cP. The specific process of tape casting may include: casting the slurry on the substrate, controlling the casting speed at 1.0-3 m / min, the casting length is 20-40 m, and drying at 50-80 ° C. The present application adopts water-based slurry, and water-based casting can avoid carbon residues of organic solvents, reduce environmental pollution, and ensure uniform distribution of thin sheets.
[0077] In some embodiments, the sintering conditions include: a sintering temperature of 1400-1700°C and a sintering time of 1-3h. Specifically, the sintering temperature can be 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, etc., and the sintering time can be 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0078] It is understandable that step-by-step heating or one-step heating can be adopted, and a cooling step is also included after sintering; for example, the heating curve can be: heating to 400-600℃ at 1-5℃ / min and keeping warm for 2-4h, and then heating to the sintering temperature at a heating rate of 1-10℃ / min. The cooling curve can be cooling to room temperature at a cooling rate of 4-6℃ / min. The sintering time has a great influence on the toughness of the material. If the sintering time is too long, the grains grow, which is not conducive to toughness. By optimizing the sintering process and reducing grain coarsening, the toughness and crack resistance of the material can be improved.
[0079] In some embodiments, the sintering step further includes a polishing step; optionally, the roughness of the ZTA ceramic substrate is ≤0.1 μm.
[0080] In some embodiments, the ZTA ceramic substrate has a flexural strength of ≥700 MPa and a thermal conductivity of ≥29 W / m·K.
[0081] The second aspect of the present application provides a ZTA ceramic substrate prepared by the aforementioned preparation method.
[0082] The third aspect of the present application provides the application of the aforementioned ZTA ceramic substrate in high-power electronic modules and semiconductor packaging.
[0083] It is worth noting that the raw materials used in the examples of the present application are all common commercially available products, and their sources are not specifically limited.
[0084] The following is an exemplary description of some raw materials:
[0085] Zirconium oxychloride (ZrOCl2·8H2O): purity ≥99%, provided by Oriental Zirconium Industry, used to provide ZrO2 source;
[0086] Aluminum nitrate (Al(NO3)3·9H2O): purity ≥99.5%, provided by Aladdin Company as the main source of Al2O3;
[0087] Surfactant: polyvinylpyrrolidone (PVP), supplied by Sinopharm Group;
[0088] The first dispersant and the second dispersant: polycarboxylate dispersant for ceramics, purchased from San Nopco Co., Ltd.;
[0089] Defoamer: a defoamer specifically for ceramic slurry, purchased from Jiazhixinnuo (Nantong) Chemical Co., Ltd.;
[0090] Binder: polyvinyl alcohol (PVA), supplied by Sinopharm Group;
[0091] Plasticizer: glycerol, commonly available in the market;
[0092] Water-retaining agent: Hydroxypropyl methylcellulose, cyclohexanone, supplied by Sinopharm Group;
[0093] Thickener: sodium carboxymethyl cellulose, supplied by Sinopharm Group;
[0094] Alumina powder: high purity alumina powder, purchased from Arteofa Aluminum (Shanghai) Co., Ltd.;
[0095] Zirconia powder: high purity zirconium oxide powder, purchased from Guangdong Oriental Zirconium Technology Co., Ltd.
[0096] The following are specific embodiments.
[0097] Example 1
[0098] A method for preparing a ZTA ceramic substrate, the steps are as follows:
[0099] 1) adding zirconium oxychloride and aluminum nitrate into deionized water in a mass ratio of 91:9, controlling the total solid dosage to 20wt%, to obtain a dispersion; adding a surfactant of 3% by weight to the dispersion, stirring at 80° C. for 60 min until the solution is completely clarified, to obtain a precursor solution;
[0100] 2) The precursor solution was transferred to a microwave reaction device with a microwave frequency of 2.45 GHz and a power of 1000 W. The precursor solution was heated at 120° C. for 30 minutes to obtain a reaction solution.
[0101] 3) Filter the reaction liquid to remove excess water and organic matter to obtain a solid product, transfer the solid product to a heating device for calcination to remove organic matter and crystal water, etc. The calcination temperature is 1150°C and the calcination time is 4 hours; after calcination, crush the solid product to obtain a first powder, and control the average particle size to be 5-10µm;
[0102] 4) Mix the first powder with alumina powder to obtain a second powder (in the second powder, the amount of zirconium oxide is 12wt%); add the second powder to a ball mill (QM-3SP2 planetary ball mill), add a dispersion medium of 23wt% of the mass of the second powder (in the dispersion medium, the mass percentages of water, the first dispersant and the defoamer are 87.0wt%, 8.7wt% and 4.3wt%, respectively), ball mill for 16 hours, and further refine the particles by sand milling to obtain a third powder, ensuring that the specific surface area is between 6-10m² / g, and the final average particle size is controlled at 0.1-0.3µm;
[0103] 5) The third powder is mixed with a binder, a plasticizer, a second dispersant, a plasticizer, a water retaining agent (cyclohexanone), a thickener and water in the following proportions to prepare a slurry:
[0104] The third powder: 45wt%;
[0105] Binder: 23.5wt%;
[0106] Second dispersant: 1.5wt%;
[0107] Plasticizer: 0.5wt%;
[0108] Water retaining agent: 1wt%;
[0109] Thickener: 1wt%;
[0110] Water: 27.5wt%.
[0111] The slurry was stirred until the viscosity reached 1500 cP, and was evenly coated into a sheet through a casting device at a speed of 1.5 m / min. The casting length was 30 m, the drying temperature was 60 ° C, and sintering was performed under the following conditions:
[0112] The sintering equipment is a Muffle furnace, which uses staged heating: heating to 500°C at a rate of 3°C / min, and then heating to a maximum temperature of 1550°C at a rate of 5°C / min, and keeping the temperature for 3 hours. After sintering, the temperature is cooled to room temperature at a rate of 5°C / min, and the sintered ceramic sheet is surface polished to a roughness of 0.1µm, thereby obtaining the ZTA ceramic substrate (thickness of 0.32mm).
[0113] Example 2
[0114] A method for preparing a ZTA ceramic substrate, the steps are as follows:
[0115] 1) adding zirconium oxychloride and aluminum nitrate into deionized water in a mass ratio of 88:12, controlling the total solid dosage to be 22wt%, to obtain a dispersion; adding a surfactant of 3.5% by weight to the dispersion, stirring at 80° C. for 60 min until the solution is completely clarified, to obtain a precursor solution;
[0116] 2) The precursor solution was transferred to a microwave reaction device with a microwave frequency of 2.45 GHz and a power of 1100 W. The precursor solution was heated at 125° C. for 35 minutes to obtain a reaction solution.
[0117] 3) Filter the reaction liquid to remove excess water and organic matter to obtain a solid product, transfer the solid product to a heating device for calcination to remove organic matter and crystal water, etc. The calcination temperature is 1200°C and the calcination time is 3.5 hours; after calcination, crush the solid product to obtain a first powder, and control the average particle size to be 5-8µm;
[0118] 4) Mix the first powder with alumina powder to obtain a second powder (in the second powder, the amount of zirconium oxide is 10wt%); add the second powder to a ball mill (QM-3SP2 planetary ball mill), add a dispersion medium of 27.5wt% of the mass of the second powder (in the dispersion medium, the mass percentages of water, the first dispersant and the defoamer are 80wt%, 16wt% and 4wt% respectively), ball mill for 18 hours, and then sand mill to further refine the particles to obtain a third powder, ensuring that the specific surface area is between 7-10m² / g, and the final average particle size is controlled at 0.15-0.25µm;
[0119] 5) The third powder is mixed with a binder, a plasticizer, a second dispersant, a plasticizer, a water retaining agent (hydroxypropyl methylcellulose), a thickener and water in the following proportions to prepare a slurry:
[0120] The third powder: 47wt%;
[0121] Binder: 20.5wt%;
[0122] Second dispersant: 1.5wt%;
[0123] Plasticizer: 2wt%;
[0124] Water retaining agent: 4wt%;
[0125] Thickener: 2wt%;
[0126] Water: 23wt%.
[0127] The slurry was stirred until the viscosity reached 1550cP, and was evenly coated into a sheet at a speed of 2m / min through a casting device. The casting length was 30m, the drying temperature was 65°C, and the sintering was performed under the following conditions: the sintering equipment was a Muffle furnace, and the temperature was raised in stages: the temperature was raised to 530°C at a rate of 2°C / min, and then the temperature was raised to a maximum temperature of 1560°C at a rate of 1.2°C / min, and the temperature was kept for 3 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 4°C / min, and the sintered ceramic sheet was surface polished to a roughness of 0.1µm, thereby obtaining the ZTA ceramic substrate (thickness of 0.32mm).
[0128] Example 3
[0129] A method for preparing a ZTA ceramic substrate, the steps are as follows:
[0130] 1) adding zirconium oxychloride and aluminum nitrate into deionized water in a mass ratio of 85:15, controlling the total solid dosage to be 22wt%, to obtain a dispersion; adding a surfactant of 3.5% by weight to the dispersion, stirring at 80° C. for 60 min until the solution is completely clarified, to obtain a precursor solution;
[0131] 2) The precursor solution was transferred to a microwave reaction device with a microwave frequency of 2.45 GHz and a power of 1100 W. The precursor solution was heated at 125° C. for 35 minutes to obtain a reaction solution.
[0132] 3) Filter the reaction liquid to remove excess water and organic matter to obtain a solid product, transfer the solid product to a heating device for calcination to remove organic matter and crystal water, etc. The calcination temperature is 1200°C and the calcination time is 3.5 hours; after calcination, crush the solid product to obtain a first powder, and control the average particle size to be 5-8µm;
[0133] 4) Mix the first powder with alumina powder to obtain a second powder (in the second powder, the amount of zirconium oxide is 11wt%); add the second powder to a ball mill (QM-3SP2 planetary ball mill), add a dispersion medium of 28wt% of the mass of the second powder (in the dispersion medium, the mass percentages of water, the first dispersant and the defoamer are 78.6wt%, 14.3wt% and 7.1wt%, respectively), ball mill for 18 hours, and further refine the particles by sand milling to obtain a third powder, ensuring that the specific surface area is between 7-10m² / g, and the final average particle size is controlled at 0.15-0.25µm;
[0134] 5) The third powder is mixed with a binder, a plasticizer, a second dispersant, a plasticizer, a water retaining agent (cyclohexanone), a thickener and water in the following proportions to prepare a slurry:
[0135] The third powder: 47wt%;
[0136] Binder: 20.5wt%;
[0137] Second dispersant: 2.5wt%;
[0138] Plasticizer: 2wt%;
[0139] Water retaining agent: 3wt%;
[0140] Thickener: 2wt%;
[0141] Water: 23wt%.
[0142] The slurry was stirred until the viscosity reached 1550cP, and was evenly coated into a sheet at a speed of 2m / min through a casting device. The casting length was 30m, the drying temperature was 65°C, and the sintering was performed under the following conditions: the sintering equipment was a Muffle furnace, and the temperature was raised in stages: the temperature was raised to 530°C at a rate of 1.5°C / min, and then the temperature was raised to a maximum temperature of 1560°C at a rate of 1°C / min, and the temperature was kept for 3 hours. After the sintering was completed, the temperature was cooled to room temperature at a cooling rate of 2°C / min, and the sintered ceramic sheet was surface polished to a roughness of 0.1µm, thereby obtaining the ZTA ceramic substrate (thickness of 0.32mm).
[0143] Comparative Example 1
[0144] Without the precursor reaction, the second powder is prepared by directly mixing zirconium oxide powder and aluminum oxide powder, that is:
[0145] Except that the second powder is directly made of zirconium oxide powder and aluminum oxide powder, the rest is the same as Example 1.
[0146] Comparative Example 2
[0147] Except that microwave heating is not used in step 2), the rest is the same as in Example 1. Step 2) is specifically as follows:
[0148] The precursor solution was transferred to a forced air drying oven and heated at 120° C. for 30 minutes to obtain a reaction solution.
[0149] Test Case
[0150] The ZTA ceramic substrates of Examples 1-3 and Comparative Examples 1-2 were cut into 45 mm×4 mm samples, and the bending strength and thermal conductivity were tested. The results are shown in Table 1.
[0151] 1. Bending strength: tested by three-point bending method, test standard is ISO 14704;
[0152] 2. Thermal conductivity: measured by laser thermal conductivity meter.
[0153] Table 1 Bending strength and thermal conductivity of Examples 1-3 and Comparative Examples 1-2
[0154]
[0155] As can be seen from Table 1, Examples 1-3 of the present application prepared ZTA ceramic substrates with good thermal conductivity and mechanical properties, with a bending strength of ≥700 MPa and a thermal conductivity of ≥29 W / m·K, which can meet the requirements of high-heat dissipation applications such as high-power electronic modules and semiconductor packaging.
[0156] Comparative Example 1 did not use a precursor reaction, but directly mixed zirconium oxide powder and aluminum oxide powder, resulting in uneven particle distribution and large grains, which resulted in lower bending strength and thermal conductivity than the examples.
[0157] Comparative Example 2 does not adopt microwave-assisted reaction, but uses traditional heating method, which leads to decreased uniformity of particle distribution, and lower bending strength and thermal conductivity than those in the embodiment.
[0158] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0159] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a ZTA ceramic substrate, characterized in that: The steps include: Dispersing zirconium salt and aluminum salt in water to prepare a dispersion; adding a surfactant to the dispersion and mixing the mixture to prepare a precursor solution; subjecting the precursor solution to a microwave-assisted reaction to prepare a reaction solution; Separating the reaction liquid into solid and liquid, taking the solid product and calcining and crushing it to prepare a first powder; Mixing the first powder with aluminum oxide to prepare a second powder; adding a dispersing medium to the second powder and grinding to prepare a third powder; Dispersing the third powder, binder, plasticizer and additive in water to prepare slurry; The slurry is tape-casted, dried, and sintered to prepare the ZTA ceramic substrate.
2. The preparation method according to claim 1, characterized in that The zirconium salt includes at least one of zirconium oxychloride, zirconium oxysulfate, zirconium nitrate, zirconium acetate, zirconium sulfate and zirconium chloride; and / or the aluminum salt comprises at least one of ammonium aluminum sulfate, aluminum nitrate and aluminum chloride; And / or the surfactant includes at least one of polyvinyl pyrrolidone, polyacrylic acid, polyacrylate, polyethylene glycol and polyvinyl alcohol.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the zirconium salt to the aluminum salt is 80:20-95:5; the added amount of the surfactant is 2-5wt% of the dispersion; and the solid dosage of the dispersion is 10-40wt%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the second powder, the amount of zirconium oxide is 6-12wt%; And / or the mass ratio of the second powder to the dispersion medium is 1:0.15-1:0.
5.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The dispersion medium comprises water, a first dispersant and a defoaming agent; Optionally, in the dispersion medium, in terms of mass percentage, the amount of water is 75-90%, the amount of the first dispersant is 5-20%, and the amount of the defoaming agent is 3-10%.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The binder includes at least one of polyvinyl alcohol, styrene-acrylic latex and acrylic latex; And / or the plasticizer includes C3-C 10 Polyols; and / or the auxiliary agent includes at least one of a second dispersant, a water retaining agent and a thickener; And / or in the slurry, based on the mass percentage of the slurry being 100%, the amount of the third powder is 40-50%, the amount of the binder is 15-25%, the amount of the plasticizer is 0.5-4%, the amount of the auxiliary agent is 2-10%, and the amount of water is the balance.
7. The preparation method according to any one of claims 1 to 3, characterized in that: The average particle size of the first powder is 3-15µm; And / or the specific surface area of the third powder is 6-10m² / g, and the average particle size of the third powder is 0.1-0.5µm.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The conditions of the microwave-assisted reaction include: microwave frequency 2-3 GHz, microwave power 800-1200 W, reaction temperature 120-180° C. and reaction time 20-60 min; And / or the calcination conditions include: calcination temperature of 1000-1400°C, calcination time of 2-6h; and / or the grinding comprises ball milling and / or sand milling; And / or the sintering conditions include: sintering temperature of 1400-1700° C., sintering time of 1-3 h.
9. A ZTA ceramic substrate prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the ZTA ceramic substrate prepared by the preparation method according to any one of claims 1 to 8 and the ZTA ceramic substrate according to claim 9 in high-power electronic modules and semiconductor packaging.